Impact of Air Fuel Mixture Formation Method on Soot Emission Volume in Ship Engine Exhaust Gas - Dmitry Glazkov (Scientific Journal of Gdynia Maritime University, 2019)
The paper discusses the mechanism and properties of the soot generation process for cases of volumetric and volumetric/film-based methods of air fuel mixture formation. Results of testing the impact of operating factors on soot emissions are shown. For selected ship engines, empirical relations between soot emissions and affecting factors are determined.